(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the political, economic and geopolitical situation of the Khiva Khanate during the reign of Shergozi Khan, especially the process of defeating the Bekovich-Cherkassky expedition sent by Peter I, based on scientific sources. The study examines the strategic goals of the Russian Empire in relation to Central Asia at the beginning of the 18th century and the military-diplomatic tactics used by Shergozikhan against them, highlighting his historical role in maintaining the security of the region. In conclusion, it is argued that Shergozikhan’s victory delayed the Russian invasion for more than a century and was a decisive factor in preserving the political sovereignty of the Khiva Khanate.